1992
DOI: 10.1088/0953-4075/25/11/021
|View full text |Cite
|
Sign up to set email alerts
|

Elastic electron scattering and rovibrational excitation of N2at low incident energies

Abstract: The scattering of low energy electrons from nitrogen has been investigated for a range of impact energies (1.5, 2.1, 3.0 and 5.0 eV) which encompass the 2 Pi g resonance. Measured differential and integral cross sections for both elastic scattering and rovibrational excitation (v=0-1, 2, 3) of the ground electronic state are compared with results from previous experimental and theoretical investigations. In some cases, particularly at 1.5 eV, significant discrepancies are found between the present and previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
29
1

Year Published

1995
1995
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 22 publications
6
29
1
Order By: Relevance
“…In this case, the number density of a vibrational level w is given by Eq. (11) and the vibrational energy of the system at a given t is…”
Section: B Anharmonic Casementioning
confidence: 99%
See 1 more Smart Citation
“…In this case, the number density of a vibrational level w is given by Eq. (11) and the vibrational energy of the system at a given t is…”
Section: B Anharmonic Casementioning
confidence: 99%
“…By the use of Eq (11). and the expressions of E v (t ) and E ¤ v (T e ), the rate of change of the vibrational energy [Eq.…”
mentioning
confidence: 99%
“…[56], Brennan et al. [57], and Shi, Stephen, and Burrow [58]; comparisons of 1050-2947/95/52(2)/1229{28)/$06. 00 1229 Qc1995 The American Physical Society the data from many of these experiments appear in the latter two papers.…”
Section: Intrqductiqnmentioning
confidence: 99%
“…The discussion given in these papers showed that the positions and shapes of resonant peaks in DCS depend sensitively on both the ®nal vibrational state and the scattering angle. However, the measurements of DCS by Brennan et al (1992) were performed at only a few energies and used a normalization technique which was revised by Sun et al (1995). Robertson et al (1997) used this new technique to calculate vibrational excitation cross sections of N 2 and found that their results are in excellent agreement with the cross sections derived from previous swarm analysis and crossed beam studies at energies above 1.5±1.7 eV, but not compatible with the drift velocity data at energies up to about 1 eV.…”
Section: Introductionmentioning
confidence: 97%
“…Comparisons of DCS for N 2 v 0 3 N 2 v 1 scattering from many of these experiments have been carried out by Brennan et al (1992) and Sun et al (1995). The discussion given in these papers showed that the positions and shapes of resonant peaks in DCS depend sensitively on both the ®nal vibrational state and the scattering angle.…”
Section: Introductionmentioning
confidence: 99%